PENGARUH FASILITAS DAN PROMOSI TERHADAP KEPUTUSAN MENGINAP DI PACIFIC PALACE HOTEL - Juherdin; Raymond (SCIENTIA JOURNAL, 2021)
The aim of this research is to analyze the impact of facilities and promotions on the decision of staying at the Pacific Palace Hotel. This research is quantitative with a population of 11,826 and a sample of 100 people obtained using the slovin formula. The questionnaire is the instrument of this research. Data processing uses SPSS 26 and from the calculation results it reveal that the facility produces tcount > ttable (3.763 > 1.9847) with a significance of 0.000 < 0.05, so the facility affects the decision to stay. And tcount (4.386 > 1.9847) ttable with a significance of 0.000 < 0.05 for the variable of promotion which means that promotion owns a positive as well as significant impact on the decision of staying. The F test results display fcount > ftable (39.278 > 2.70) with a significance of 0.00 < 0.05, so facilities and promotions own a positive and significant effect on the stay decision. The value of R Square is 0.447.